Short Communication: Occurrence of leaf spot diseases on Aloe vera (L.) Burm.f. caused by Curvularia species from Madhya Pradesh, India - SHUBHI AVASTHI; AJAY KUMAR GAUTAM; REKHA BHADAURIA (Biodiversitas Journal of Biological Diversity, 2015)
Avasthi S, GautamAK, Bhadauria R. 2015. Occurrence of leaf spot diseases on Aloe vera (L.) Burm.f. caused by Curvularia species from Madhya Pradesh, India. Biodiversitas 16: 79-83. During 2010-2011, occurrence of leaf spot diseases was observed on Aloevera plants grown in various nurseries of Gwalior, Madhya Pradesh, India. The typical disease symptoms were observed on the abaxialsurface, tips and spiny margins of leaves. Disease spots were sunken, dry, necrotic, dark maroon to dark brown in color. On the basis ofmorphological and microscopic characteristics of the fungus, two species of Curvularia i.e. Curvularia lunata and Curvularia ovoidea,were found to be associated with the leaf spot diseases. Koch’s postulate was applied to confirm the causal organisms of the diseases.According to the literature, this is the first report of leaf spot disease on A. vera caused by Curvularia lunata from Madhya Pradesh, andthe first report of Curvularia ovoidea from India.